Ordinances of the City Council of Charleston, in the State of South-Carolina, Passed since the Incorporation of the City, Collected and Revised Pursuant to a Resolution of the Council, at 153, No. 145, § 5 (1802) - (:unkn) unknown (General Publisher, 1802)
That it shall and may be lawful for the fire-masters to enter into the houses, out-houses, stables and yards of every owner or tenant of the same in Charleston, wherever they shall see occasion and enquire, search, and examine if any quantities of gun-powder ,hay, straw, fodder, pitch, tar, rosin, turpentine, hemp, oil, tallow, or other combustible matter, are lodged in any such place within the said city, which may be in danger of taking fire; and if the said fire-masters shall find there is apparent danger that fire may be communicated by such combustibles, they shall admonish the owner or the tenant of such house or houses, to remove the same
--
Keywords: GUN POWDER STORAGE